Rhodium(iii)-catalyzed switchable C–H acylmethylation and annulation of 2, 2′-bipyridine derivatives with sulfoxonium ylides. Issue 19 (28th April 2021) - Chen, Mengjia; Meng, Haifang; Yang, Fang; Wang, Yani; Chen, Chen; Zhu, Bolin
Abstract : A novel protocol for Rh(iii )-catalyzed switchable C–H acylmethylation and annulation of 2, 2′-bipyridine derivatives with sulfoxonium ylides was described. Abstract : A novel protocol for Rh(iii )-catalyzed switchable C–H acylmethylation and annulation of 2, 2′-bipyridine derivatives with sulfoxonium ylides is reported. This protocol provides a facile approach to synthesize structurally diverse acylmethylated 2, 2′-bipyridine derivatives and acyl pyrido[2, 3- a ]indolizines with a broad range of functional group tolerance.